PENGARUH BRAND EQUITY DAN PRICING TERHADAP PURCHASE INTENTION MASKAPAI LOW COST CARRIER DI JAKARTA - Sherly Wowor; Andy Lunarjanto (Journal of Business Strategy and Execution, 2014)
Low cost carrier flight industry has negative issues recently in Indonesia, for example pilots were identified for drugs problems, many flight cancellation and delay, issues of consumer convenience such as stiff padding and knee-knocking issues and other issues which affects the brand equity of the airline industry itself. Based on the theory, brand equity is an important and valuable asset to a company, since it can affect a long-term relationship between producers and consumers. Thus, bad branding-decision will destroy the business. Therefore, if the company is able to have a good branding, it will increase company’s performance. Customer based brand equity reflects on how customers think, feel, and appreciate a brand as well as price, market share, and the advantages given to a company's brand. The aim of this study was to determine the influence of brand awareness, brand association and price airline tickets low cost carrier flight in Jakarta on purchase intention. The method used was a descriptive correlation method based on hypothesis testing to determine the level of relationship variables as well as the magnitude of the relationship. Results from this study indicate that there is a significant influence of brand awareness, brand association and the price on the purchase intention. However, price has the greatest influence on the purchase intention (0.343) followed by brand association (0.248) and then brand awareness (0,211).